Affective Scholarship: Doing Anthropology with Epistemic Affects. (29th October 2018) - Stodulka, Thomas; Selim, Nasima; Mattes, Dominik
Abstract: This article discusses the potential of fieldworkers' affects as epistemic processes. It showcases lessons from long‐term fieldwork in diverse geographical locations (Indonesia, Germany, and Tanzania) and insights from our affective inquiries into coming of age on the streets, Sufism, and antiretroviral HIV‐therapy. Inspired by ethnographic writings relating to psychological anthropology and the "affective turn, " we propose epistemic affects as a core analytical means for venturing into a nuanced understanding of the processes, situations, persons, communities, and places we study (with). The article defines epistemic affect, situates it in contemporary debates on how to make affect epistemologically productive, and offers several field episodes to illustrate how affects might open up empirically robust ways of knowing. Finally, it introduces the broader idea of affective scholarship, which advocates systematic explorations of anthropologists' relational engagements with interlocutors, the practices they study, and the things and places they encounter. [affect, emotion, epistemology, ethnography, fieldwork, method]